El monumento funerario como reflejo del status socioeconómico. Un ejemplo concreto: Asturica Augusta, Bracara Augusta y Lucus Augusti - García Martínez, Sonia María (Estudios humanísticos. Geografía, historia y arte, 1996)
In this article, we are going to analize the socioeconomic differences that exist inside each conventual capital of the Hispanic-roman Northwest (Asturica Augusta, Bracara Augusta y Lucus Augusti) taking as specimen the funerary monuments remaining from the Roman period as they reflect both the religious belief and the social position of the deceased and of the person who dedicates the epitaph.